2020
DOI: 10.1038/s41467-020-20262-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human RNA polymerase III

Abstract: In eukaryotes, RNA Polymerase (Pol) III is specialized for the transcription of tRNAs and other short, untranslated RNAs. Pol III is a determinant of cellular growth and lifespan across eukaryotes. Upregulation of Pol III transcription is observed in cancer and causative Pol III mutations have been described in neurodevelopmental disorders and hypersensitivity to viral infection. Here, we report a cryo-EM reconstruction at 4.0 Å of human Pol III, allowing mapping and rationalization of reported genetic mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Although the cellular pathophysiological mechanisms associated with POLR3-HLD have yet to be uncovered, studies have shown that mutations in POLR3 subunits can cause disruptions on several molecular levels. For example, mutational mapping onto specific protein domains suggests association with specific mechanisms of dysfunction, including modification of the catalytic cleft structure, impaired POLR3 complex assembly, perturbed interactions between subunits, and interference within POLR3 complex binding to DNA (Bernard et al, 2011 ; Tétreault et al, 2011 ; Girbig et al, 2020 ; Ramsay et al, 2020 ). Additionally, protein localization studies have shown that disease-causing POLR1C variants can alter assembly and nuclear import exclusively of POLR3, resulting in a lack in binding to POLR3 target genes (Thiffault et al, 2015 ).…”
Section: Polr3-related Leukodystrophy: Approaching Treatment Optionsmentioning
confidence: 99%
“…Although the cellular pathophysiological mechanisms associated with POLR3-HLD have yet to be uncovered, studies have shown that mutations in POLR3 subunits can cause disruptions on several molecular levels. For example, mutational mapping onto specific protein domains suggests association with specific mechanisms of dysfunction, including modification of the catalytic cleft structure, impaired POLR3 complex assembly, perturbed interactions between subunits, and interference within POLR3 complex binding to DNA (Bernard et al, 2011 ; Tétreault et al, 2011 ; Girbig et al, 2020 ; Ramsay et al, 2020 ). Additionally, protein localization studies have shown that disease-causing POLR1C variants can alter assembly and nuclear import exclusively of POLR3, resulting in a lack in binding to POLR3 target genes (Thiffault et al, 2015 ).…”
Section: Polr3-related Leukodystrophy: Approaching Treatment Optionsmentioning
confidence: 99%
“…Moreover, knockdown of RNase P leads to a decrease in the binding of RPC6 and RPC7 to 5S rRNA and tRNA gene loci [73]. This finding highlights the necessity for an intact RNase P in formation of the initiation subcomplex, which is positioned close to the start point of transcription [52,66,67,68,100].…”
Section: Main Sectionsmentioning
confidence: 94%
“…Pol III has seventeen protein subunits [60][61][62], three of which form a specific subcomplex, RPC3-RPC6-RPC7, implicated in promoter-dependent initiation and elongation [52,62,63,64,65,66,67]. The cryo-EM structure of human Pol III reveals several species-specific modules that mediate activation and repression of transcription [64,65,68]. The core transcription factors TFIIIA, TFIIIB, TFIIIC, and SNAPc assemble diverse initiation complexes of Pol III on target genes with various types of promoters and auxiliary cis-acting sequences [51,53,54,61,63,69,70].…”
Section: Main Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they all share five subunits (Rpb5, Rpb6, Rpb8, Rpb10, and Rpb12) with common functions but also with specific roles in their corresponding RNAPs (Cramer et al, 2008;Cuevas-Bermúdez et al, 2017). The structures of the three eukaryotic RNAPs, first solved in Saccharomyces cerevisiae, are highly conserved and their resolution has tremendously helped to understand the mechanism of transcription (Cramer et al, 2000;Armache et al, 2005;Engel et al, 2013;Fernandez-Tornero et al, 2013;Hoffmann et al, 2015;Sainsbury et al, 2015;Ramsay et al, 2020;Schier and Taatjes, 2020). The correct regulation of gene transcription depends on mechanisms that regulate the formation of large multiprotein complexes (RNAPs and their cognate factors) and their dynamics through all the transcription process.…”
Section: Introductionmentioning
confidence: 99%